(untitled) (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Preeclampsia (PE) is a pregnancy-specific disorder characterized by hypertension and multiorgan dysfunction, affecting 2-8% of pregnancies and posing significant risks for maternal and fetal health. This study investigates the association between the neutrophil-lymphocyte ratio (NLR) and preeclampsia, aiming to explore NLR’s potential as a cost-effective biomarker for early diagnosis. Methods: This cross-sectional study was conducted at Sir Salimullah Medical College Mitford Hospital, Dhaka, over 12 a period of months The study included a total of 78 singleton pregnant women, aged 18 to 35, and between 28 to 40 weeks of gestation. While the case group consisted of 26 women diagnosed with preeclampsia, the control group formed of 52 healthy pregnant women. Pregnant women with known comorbidities, including diabetes, hypertension, hypothyroidism, systemic lupus erythematosus (SLE), or any maternal infections (e.g., respiratory tract infections, urinary tract infections) were excluded from the study. Results: More than 40% of women with preeclampsia were aged 25 to 30 years, while nearly half of the control group were aged 18 to 25. No significant age difference was found between groups (27.3 ± 5.3 vs. 35.8 ± 3.3, p = 0.184). The case group exhibited significantly higher absolute neutrophil counts (6.83 ± 1.39 vs. 5.56 ± 1.19 ×10^9/L, p < 0.001) and NLR (3.7 ± 0.4 vs. 3.0 ± 0.6, p < 0.001) compared to controls. Significant positive correlations were observed between NLR and both systolic (r = 0.490, p < 0.001) and diastolic blood pressures (r = 0.587, p < 0.001). Conclusion: Our findings suggest that elevated NLR is associated with preeclampsia and may serve as a valuable biomarker for its diagnosis. The study highlights the importance of NLR in enhancing early detection and management of preeclampsia, particularly in resource-limited settings. Ibrahim Card Med J 2024; 14(1): 35-39